Electronic and mechanical design of a hexapod land searching robot - (:unkn) unknown (My University, 2020)
In this study, it is aimed to design a robot that can be used in fields such as land exploration, minesearch, ammunition transportation, search and rescue activities in natural disasters. For thispurpose, a six-legged robot was designed. The robot can move evenly in uneven terrain conditions,stop, accelerate and overcome the obstacle when it sees an obstacle. The mechanical and electronicdesign of the robot was realized, and a prototype was manufactured. The flexibility of the legsused in the design ensures that the robot can move more easily in field conditions. The synchronousspeed and direction of the motors are controlled, and the robot moves in a balanced way. With theIP camera mounted on a Raspberry Pi, snapshots were taken from the robot. Mechanical andelectronic design of six-legged robot capable of moving on uneven ground was realized. The sixlegged robot was placed with three legs on the right and three legs on the left. The motors wereoperated simultaneously to allow the robot to move evenly. Thanks to its leg structure, it wasaimed to travel in land conditions. Image control was provided on the computer with the cameraplaced on the robot. In this study, the program written into the electronic cards run the motorssimultaneously.
Keywords: Mimarlık; Hücre ve Doku Mühendisliği; Bilgisayar Bilimleri, Yapay Zeka; Bilgisayar Bilimleri, Donanım ve Mimari; Bilgisayar Bilimleri, Bilgi Sistemleri; Bilgisayar Bilimleri, Yazılım Mühendisliği; Bilgisayar Bilimleri, Teori ve Metotlar; İnşaat ve Yapı Teknolojisi; Enerji ve Yakıtlar; Mühendislik, Hava ve Uzay; Mühendislik, Biyotıp; Mühendislik, Kimya; İnşaat Mühendisliği; Mühendislik, Elektrik ve Elektronik; Çevre Mühendisliği; Mühendislik, Jeoloji; Endüstri Mühendisliği; İmalat Mühendisliği; Mühendislik, Deniz; Mühendislik, Makine; Mühendislik, Petrol; Gıda Bilimi ve Teknolojisi; Jeoloji; Yeşil, Sürdürülebilir Bilim ve Teknoloji; Görüntüleme Bilimi ve Fotoğraf Teknolojisi; Denizcilik; Malzeme Bilimleri, Biyomalzemeler; Malzeme Bilimleri, Özellik ve Test; Malzeme Bilimleri, Kaplamalar ve Filmler; Malzeme Bilimleri, Kompozitler; Malzeme Bilimleri, Tekstil; Maden İşletme ve Cevher Hazırlama; Nanobilim ve Nanoteknoloji; Robotik; Taşınım Bilimi ve Teknolojisi